Strengthening Democratic Elections and Quality in Indonesia - Sri Hastuti Puspitasari; Mahrus Ali (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
General election, a vital indicator of a democratic country like Indonesia, has been implemented since 1955, but its realization as a truly democratic process remains questionable. The purpose of this research is to examine the standards of democratic, quality and ways to strengthen election in Indonesia. The research uses a normative approach, utilizing secondary data and both juridical and conceptual approaches. The juridical approach is employed due to the legal aspects of the research object, while the conceptual approach is utilized to understand the concepts of Democratic and Qualified Elections. The data, which is in the form of descriptions, is analyzed in a qualitative descriptive manner. It is concluded that the realization of democratic and quality elections in Indonesia is highly dependent on several factors, including the state, election participants, and citizens as voters